2021
DOI: 10.1515/nanoph-2021-0520
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz toroidal metasurface biosensor for sensitive distinction of lung cancer cells

Abstract: Lung cancer is the most frequently life-threatening disease and the prominent cause of cancer-related mortality among human beings worldwide, where poor early diagnosis and expensive detection costs are considered as significant reasons. Here, we try to tackle this issue by proposing a novel label-free and low-cost strategy for rapid detection and distinction of lung cancer cells relying on plasmonic toroidal metasurfaces at terahertz frequencies. Three disjoint regions are displayed in identifiable intensity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(34 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…The THz regime is strongly sensitive to the presence of water molecules, which offers the possibility to identify a cancer cell by exploiting the difference in the water content between normal and cancer cells. Chiben Zhang et al [ 203 ] reported the identification of lung cancer cells by using metasurface operating in the THz band. The structure was made from a pair of split-ring resonators (SRRs) placed by facing the gap closed to each other with a 2.5 µm separation, as shown in Figure 9 a. Additionally, on the opposite side of the ring, a small gap is also introduced to the structure.…”
Section: Application Of Metasurfaces For Biosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The THz regime is strongly sensitive to the presence of water molecules, which offers the possibility to identify a cancer cell by exploiting the difference in the water content between normal and cancer cells. Chiben Zhang et al [ 203 ] reported the identification of lung cancer cells by using metasurface operating in the THz band. The structure was made from a pair of split-ring resonators (SRRs) placed by facing the gap closed to each other with a 2.5 µm separation, as shown in Figure 9 a. Additionally, on the opposite side of the ring, a small gap is also introduced to the structure.…”
Section: Application Of Metasurfaces For Biosensingmentioning
confidence: 99%
“…The sensitivity was reported as 485.3 GHz/RIU. The effect of height and dielectric dissipation are also investigated, and further details can be found in [ 203 ]. In the experimental part, to measure lung cancer, three different types of lung cancer were considered, i.e., Calu-1, A427, and 95D.…”
Section: Application Of Metasurfaces For Biosensingmentioning
confidence: 99%
“…Metamaterial-based THz sensor can provide the sensitive detection of the analyte owing to their localized field enhancement properties; exhibiting the variation of the dielectric environment will induce the obvious change of sensing spectra involved with the resonant frequency and linewidth [31,32]. Recent excellent studies show the apparent shifts of both the resonant frequency and depth can be observed in THz toroidal metasurface for sensitive distinction of lung cancer cells [33]. The EIT-like resonance can experience frequency and magnitude variations when the properties of analytes change, showing that the glioma cells can be distinguished directly based on this EIT resonance [34].…”
Section: Introductionmentioning
confidence: 99%
“…A metamaterial is a kind of periodic artificial structure that is composed of sub-wavelength resonant units. Its electromagnetic properties can be artificially controlled by designing its unit cell and it holds important application values in electromagnetic stealth, plate focusing, polarization conversion, and direction modulation [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. The metamaterial absorber is an important research aspect of a metamaterial.…”
Section: Introductionmentioning
confidence: 99%